(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The availability of electricity in Nigeria has continued to worsen over the years, creating constraints on the country's economic growth. The country has been unable to meet demand because of its policies, regulations, management of operations, and electricity espionage accomplished by unscrupulous persons tapping into the numerous power supply networks. The present study examined the correlation between the trends in energy theft among users and the quality of power supply in Edo state, Nigeria. The study employed a correlational method to ascertain the correlation between energy theft and power supply in Edo state, Nigeria. The study population comprised energy consumers within the residential category established by the BEDC. A random sample of 277 residential consumers and BEDC employees completed the research questionnaires. The finding shows that 31.2% of the energy consumers showed they never participated in energy theft, while 68.8% showed high involvement. A Pearson's product-moment correlation was conducted to determine the correlation between energy theft and power supply quality in Edo state. The result revealed that the relationship is linear, both variables were normally distributed as calculated by Shapiro-Wilk's test (p > .05), and there were no outliers. There was a statistically significant, moderate positive correlation between energy theft and power supply quality in Edo state, r (275) = .41, p < .001. Most importantly, observation of the R2 revealed that energy theft explained about 11.6% of the variation in power supply quality in Edo state. The outcome offers the government and the electrical authorities helpful information.